The Effects of Profitability, Leverage, Activity, and Company Size on Financial Distress - Syahirotul Ambar Maulidiyah; Eni Wuryani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This research investigates how profitability, leverage, activity levels, and company scale impact financial distress in property and real estate firms traded on the Indonesia Stock Exchange. The selection of this sector stems from its high exposure to economic ups and downs, leaving its businesses particularly prone to financial troubles. Independent factors in the analysis include profitability, leverage, activity, and firm size, with financial distress serving as the outcome variable. Samples were drawn via purposive sampling from property and real estate entities listed on the Indonesia Stock Exchange over the 2022–2024 timeframe. Adopting a quantitative design, the study applies multiple linear regression as its core analytical tool. STATA version 17 handled the data analysis. Results show that, taken together, the independent variables exert a significant impact on financial distress. Ultimately, firms should optimize their financial metrics and pursue business growth to mitigate financial distress risks.